Fuzzy type 1 PID controllers design for TCP/AQM wireless networks - Manal Kadhim Oudah; Mohammed Qasim Sulttan; Salam Waley Shneen (Institute of Advanced Engineering and Science, 2021)
The search of FLC_PID controller for TCP/AQM Wireless Networks, to deal with congestion for Internet users and to get good performance and capabilities of TCP / IP networks. Neglect of controlling the network delay and the number of continuous users that leads to a problem in the transmission process. Recently, automatic control units are adapted to solve this problem with the difficulty of controlling congestion in the presence of wireless links. This modest research presents one of the traditional PID controller methods with fuzzy logic so that wireless networks and congestion can be controlled by various configurations. The proposed methods were simulated with the required comparisons in the adoption of nonlinear systems to determine the best performance and it was found that the use of the Fuzzy logic control can achieve the best performance (reducing the delay time of delivering packets and packets loss). The simulation of the current work shows through its results the possibility of controlling the behavior of the system and through testing the balance when changed with time delay through the impact of communication time and its relationship with the stability of the work of the system.